Penelitian Observasi Partisipatif Bentuk Komunikasi Interkultural Pelajar Internasional Embassy English Brighton, United Kingdom - Sejati, Veny Ari (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2019)
Data collection through participatory observation as participant moderate Intercultural communication form learners International Embassy English Brighton focus on verbal and nonverbal behavior, attitudes, or perceptions of people of different cultures and background of science and language. formal verbal communication when information comes from formal sources such as center directors, course queries, student services, counselor, lectures, students in the classroom (one to many) and one to one with face-to-face and brochure tools.Â  Informal communication occurs when students meet other students such as cafeterias, worship rooms, weekends together, and speak the primary language when meeting students from the same country.International students Embassy English Brighton comes from various non-speaking English countries. These students are generally studying for work purposes and to continue studying in major English-speaking countries such as Australia, America and the United Kingdom.